The Association between Physical Fitness Performance and Abdominal Obesity Risk among Taiwanese Adults: A Cross-Sectional Study - Lee, Po-Fu; Ho, Chien-Chang; Kan, Nai-Wen; Yeh, Ding-Peng; Chang, Yun-Chi; Li, Yu-Jui; Tseng, Ching-Yu; Hsieh, Xin-Yu; Chiu, Chih-Hui (International Journal of Environmental Research and Public Health, 2020)
The present study aims to investigate the associations between physical fitness performance and abdominal obesity risk among Taiwanese adults. We conducted a cross-sectional study and reviewed the data derived from the National Physical Fitness Survey in Taiwan (HPFSIT). Data from a total of 62,486 respondents aged 23–64 years were collected in this study. The participants completed a standardized structural questionnaire and a series of anthropometric characteristics (body mass index and waist-to-hip ratio) and physical fitness (3-min step tests, 1-min sit-up tests, and sit-and-reach tests) assessments. Waist circumference was used to define abdominal obesity status. A multiple logistic regression analysis was conducted. Our results presented almost entirely significant associations (except for women) on the 3-min step test. Moreover, the results suggest that muscular strength, endurance, and flexibility may be effective predictors of abdominal obesity among men and women, whereas cardiorespiratory fitness predicted abdominal obesity only in men. According to the results of this study, the fitness–abdominal obesity associations are minor based on a mixed population analysis. However, dose–response relationships have been observed. The present study provides a new perspective by using different types of fitness performance to predict abdominal obesity.